2018
DOI: 10.5812/ijpbs.64097
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Reliability of the Mindfulness Attention Awareness Scale for Adolescents and the Relationship Between Mindfulness and Anxiety in Adolescents

Abstract: Background: In recent years, application and practice of mindfulness-based interventions to reduce adolescent psychological problems are increasing. Therefore, it is necessary to design and study tools that measure mindfulness and its effects. Objectives: One of the available tools to measure mindfulness in adolescents is the mindfulness attention awareness scale for adolescents (MAAS-A). The current study aimed at examining the factor structure and reliability of a Persian version of this scale and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It is noteworthy to mention that mindfulness leads to acceptance of thoughts, feelings, and physical sensations without any judgments as well as a widespread awareness of them ( 48 , 49 ). Individuals can also become aware of their ruminations over the past and the future through mindfulness-based practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that mindfulness leads to acceptance of thoughts, feelings, and physical sensations without any judgments as well as a widespread awareness of them ( 48 , 49 ). Individuals can also become aware of their ruminations over the past and the future through mindfulness-based practices.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals can also become aware of their ruminations over the past and the future through mindfulness-based practices. Using this insight, they gain control over their own thoughts, feelings, and sensations, and also become free from the automatic focus on the past and the future ( 49 ). Patients with cancer can consequently feel relaxed through meditation as a basic technique in MBCT.…”
Section: Discussionmentioning
confidence: 99%
“…As comparing with prior studies on MAAS psychometric properties [ 19 , 22 , 23 , 29 , 30 ], our results share similar CFA results, which indicate that the MAAS is valid in a one-factor structure. However, a previous Iran study showed that the Persian MAAS has a two-factor structure [ 32 ]. A possible reason for the different structure findings may be due to the studied samples.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for the different structure findings may be due to the studied samples. Mohsenabadi et al [ 32 ] examined the psychometric properties of the MAAS on a sample of adolescents aged between 12 and 18 years. On the other hand, prior studies showing the one-factor structure of MAAS examined its psychometric properties on young adults (e.g., university students) [ 19 , 22 , 23 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation